Morphology and environment in some fossil Hominoids and Pedetids (Mammalia). Issue 4 (28th December 2015) - Senut, Brigitte
Abstract: Linking the environment to functional anatomy is not an easy exercise, especially when dealing with fossils, which are often fragmentary and represent animals that are extinct. A holistic approach permits us to fill the gaps in reconstructing the evolutionary patterns in fossil groups. Identifying the environment where animals lived can help to interpret some anatomical structures and, vice versa, the functional morphological pattern can help to refine some fossil environments. Two examples focusing on locomotor behaviours in fossil mammals are considered in this paper: the hominoids and the origins of hominid bipedalism and the springing adaptations in fossil rodents (Pedetidae) in connection with different habitats. In the first case, the limits of the chimp‐based models and the necessity to take into account detailed environmental reconstructions will be addressed. The famous 'savannah hypothesis' is no longer tenable because the palaeontological data support a more vegetated environment for the origins of bipedal hominids. Data from the environment will be considered. The earliest putative hominid fossils which preserve skeletal remains of the locomotor apparatus show mixed adaptations to terrestrial bipedalism and arboreal activities. The second example focuses on the variation in springing adaptations in Pedetidae in the Lower Miocene of East Africa and Southern Africa. In the East, the sites where Pedetidae were preserved were mainly forested, whereas in the South the region was more open and drier, with extensive grassy patches. In the first case, pedetids were robust and heavy jumpers, whereas in the South they were smaller, their skeleton more gracile and their springing was lighter. During the desertification of the southern part of Africa, the large pedetid species became extinct, but a smaller species developed. In the case of primates, as in the case of rodents, the skeletal morphology was adapted to its environment.